DEMATERIALIZATION OF THE CREDIT TITLE: CHALLENGES IN THE ELECTRONIC AGE (REMUNOM, 2024)
This article investigates the evolution of credit securities in an increasingly digital context. Our objective is to understand how this transition to the electronic environment affects the traditional cartular modality. To do this, we carried out exploratory research, reviewing literature and applying the hypothetical-deductive method. We analyze the compatibility between the electronic form and the principle of cartularity, in addition to discussing the challenges of dematerializing these titles. Technological development has profoundly impacted society and commercial relations, generating debates about the legitimacy of electronic securities. Questions about representativeness and lack of tangibility arise, affecting its execution and circulation. Despite the conflicts arising from computerization, we recognize the need to adequately protect these legal instruments, adapting the Law to social changes.